Pengembangan E-Modul Berbasis Flip Book Berdasarkan Model Plomp Materi Segi Empat - Yunus, Silvani; Abbas, Nurhayati; Djakaria, Ismail (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This research aims to develop a flip book-based e-module for mathematics learning media on rectangular material. This is a research and development aiming to produce a product using the Plomp development model. The subjects of this research are the students in grade VII of SMP Negeri 2 Kwandang. The finding shows that the validity assessment by the material expert and media validators for the e-module obtains an average score of 4,25 and 4,43 respectively. In addition, the assessment of teachers and students on flip book-based e-module on rectangular material obtains positive responses with an average percentage from teachers of 85,39% and from students of 79,85%. The average percentage of positive responses from teachers and student assessment in the very good category, so the e-module can be concluded that the flip book-based e-module for mathematics on rectangular material meets the validity and practicality criteria so that it is suitable for use in learning.